Islamic Arts in Imperial Collections - Shaw, Wendy M. K (Possessors and Possessed, 2003)
In 1889 a directive issued by the Council of State (Şura-ye Devlet) set out the administrative program and the organizational practices of the Imperial Museum. The collections were to be organized as follows: The Imperial Museum is divided into six parts. The first is for Greek, Roman, and Byzantine antiquities. The second is for Assyrian, Caledonian, Egyptian, Phoenician, Hittite, and Himariote antiquities, as well as for works by Asian and African tribes. The third is for works of Islamic fine arts. The fourth is for ancient coins. The fifth is for examples of natural history. The sixth is for the